2018
DOI: 10.1186/s13018-018-0903-1
|View full text |Cite
|
Sign up to set email alerts
|

WALANT for distal radius fracture: open reduction with plating fixation via wide-awake local anesthesia with no tourniquet

Abstract: BackgroundThe wide-awake local anesthesia no tourniquet (WALANT) technique is applied during various hand surgeries. We investigated the perioperative variables and clinical outcomes of open reduction and internal fixation (ORIF) for distal radius fractures under WALANT.MethodsFrom January 2015 to January 2017, 60 patients with distal radius fractures were treated, and 24 patients (40% of all) were treated with either a volar or a dorsal plate via WALANT procedure. Of these 24 patients, 21 radius fractures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 34 publications
1
71
1
Order By: Relevance
“…Moreover, we performed all procedures without the aid of surgical loupes, which could have promoted optimal tissue handling and dissection, and thus prevented iatrogenic soft tissue injury and wound complications. Although the low postoperative pain scores we found, in addition to those found by Huang et al in their study [ 1 ], they must lay support to the latter authors' findings of significantly lower mean postoperative pain score under WALANT, in their subsequent comparative study on 47 distal radius fractures treated by volar plating, under either WALANT or general anesthesia with arm tourniquet [ 7 ].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Moreover, we performed all procedures without the aid of surgical loupes, which could have promoted optimal tissue handling and dissection, and thus prevented iatrogenic soft tissue injury and wound complications. Although the low postoperative pain scores we found, in addition to those found by Huang et al in their study [ 1 ], they must lay support to the latter authors' findings of significantly lower mean postoperative pain score under WALANT, in their subsequent comparative study on 47 distal radius fractures treated by volar plating, under either WALANT or general anesthesia with arm tourniquet [ 7 ].…”
Section: Discussionsupporting
confidence: 80%
“…The neuroma was conservatively treated with 150 mg of oral pregabalin (LYRICA ® ; Pfizer, Inc., New York City, USA) daily for a week, which completely resolved the pain thereafter. Huang et al [ 1 ], in a retrospective analysis of 24 distal radius fractures treated by open reduction and plating under WALANT, documented no complications following a mean follow-up period of 15 months. In contrast to Huang et al's study, the complication rate (9%) we found in our series must be high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WALANT offers technical simplicity, and the whole procedure can be performed by a surgeon without the use of sedation. In recent few years, the WALANT technique has been employed for bony procedures, such as open reduction plating for distal radius fracture [4][5][6][7] , olecranon fracture 8 , and ankle fracture 9 . Because of no major complications, previous studies 6,8 have concluded that WALANT is a safe and simple option for patients with a high-grade anesthesia or sedation risk.…”
Section: Introductionmentioning
confidence: 99%